HUBUNGAN ANTARA KESEIMBANGAN DAN KELINCAHAN PADA ANAK SEKOLAH DASAR - Helmalia Fayza Zahra (2023)
Background: Balance has a significant effect and is the most basic skill in child growth. A high balance level results in efficient and effective movement. In this aspect the need for physical activity is agility. Agility is an indicator that gross motor skills in children are well developed. Agility has the most prominent effect on balance, creating efficient and effective movements when making movements in the opposite direction. In addition, balance and agility have far reaching effects on quality of life. Objective: The purpose of this study was to determine the relationship between balance and agility in elementary school children. Methods: The research method used was quantitative correlation with a cross sectional approach. A total of 130 students of SD Negeri 02 Girijaya Garut participated in this study, the parameters used were Standing Balance Test to assess the level of balance and Shuttle Run to assess the level of agility. Results: Based on the results of data processing using SPSS 27.0, it was found that 91 out of 130 respondents (70.0%) got a good balance score, after the correlation test was obtained correlation coefficient Spearman's Rho balance and agility p =<0.001. Conclusion: The conclusion based on this study is that there is a relationship between balance and agility in elementary school children.